2020
DOI: 10.1155/2020/9501760
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Validation of a Convenient Clinical Nomogram to Predict the Risk of Brain Metastasis in Renal Cell Carcinoma Patients

Abstract: Brain metastasis (BM) is a typical type of metastasis in renal cell carcinoma (RCC) patients. The early detection of BM is likely a crucial step for RCC patients to receive appropriate treatment and prolong their overall survival. The aim of this study was to identify the independent predictors of BM and construct a nomogram to predict the risk of BM. Demographic and clinicopathological data were obtained from the Surveillance, Epidemiology, and End Results (SEER) database for RCC patients between 2010 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 29 publications
(26 reference statements)
0
13
0
Order By: Relevance
“…The nomogram is a statistical tool; it can combine all independent risk factors to evaluate the endpoint accident in which we are interested. Nowadays, nomograms have been widely applied to predict the metastasis of other cancer patients such as renal cell carcinoma [ 9 ], gastrointestinal stromal tumor [ 10 ], and thyroid carcinoma [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The nomogram is a statistical tool; it can combine all independent risk factors to evaluate the endpoint accident in which we are interested. Nowadays, nomograms have been widely applied to predict the metastasis of other cancer patients such as renal cell carcinoma [ 9 ], gastrointestinal stromal tumor [ 10 ], and thyroid carcinoma [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Naito et al retrospectively examined the benefits of routine BM screening using computed tomography (CT) in the era of targeted therapy. 3 They showed that routine head CT significantly decreased the incidence of craniotomy, possibly indicating that the size of BMs at the time of diagnosis was larger in the non-screening group. However, no survival benefit was detected from the routine BM screening, as previously reported in the literature.…”
Section: Conflict Of Interestmentioning
confidence: 98%
“…The alternative strategy is the risk‐based approach to detecting brain metastasis. A recent study investigated the risk factors for brain metastasis, including 42 577 patients with RCC using the Surveillance, Epidemiology, and End Results (SEER) database 3 . The authors of that study found that histological type (clear cell carcinoma), tumor size (larger), bone metastasis (positive), and lung metastasis (positive) were independent risk factors for brain metastasis.…”
mentioning
confidence: 99%
“…Brain metastases (BM) is generally associated with a very poor prognosis and high degree of morbidity, requiring urgent multidisciplinary care, and is relatively unresponsive to conventional systemic therapy [11,[16][17][18][19][20][21][22][23][24][25]. BM is also a serious condition that causes headaches, focal neurological deficits, altered mental status or gradual cognitive impairment, epileptic seizures driven by increased intracranial pressure by vasogenic edema, or alterations in cerebrospinal fluid (CSF) flow, thereby impairing the quality of life (QOL) [11,[17][18][19][25][26][27]. Unfortunately, BM is not a rare finding in mRCC (8%-15%), and its prevalence has increased in the past two decades [16][17][18][19][20][21][22].…”
Section: Clinical Implications and Unmet Needs Of Brain Metastases From Rccmentioning
confidence: 99%
“…The median OS of RCC patients with BM (RCC-BM) is only 5-8 months [16][17][18][19][20][21][22]. Therefore, early detection and effective treatment of BM is an unmet medical need for mRCC [11,17,19,25]. Improved clinical outcomes of extracranial metastases by the introduction of TKIs and immune checkpoint inhibitors (ICIs) has led to the adoption of improved imaging techniques for BM, thereby increasing awareness of the benefit of brain screening [11,[17][18][19][20]27].…”
Section: Clinical Implications and Unmet Needs Of Brain Metastases From Rccmentioning
confidence: 99%